"All that's best of dark and bright": Day and night perceptions of Hong Kong cityscape. (June 2018) - Huang, Wei-Jue; Wang, Philip
Abstract: Tourists can go sightseeing at various hours of the day. This study compared visitors' perceptions of the same "sight" at daytime and nighttime, and examined how perceptions relate to visitor characteristics (i.e., nationality and circadian rhythm). Focus groups were conducted to identify the day and night brand personality of the cityscape of Hong Kong as seen from atop Victoria Peak. Afterwards, a quasi-experimental design was employed, with day-or-night video of the view as the treatment variable. Questionnaires were administered in Hong Kong and the United States for cross-cultural comparison. More significant differences were observed in the Hong Kong sample than in the USA sample. Findings revealed that "night" had more personality, in that the night view generally received higher ratings. "Day" had a more distinctive personality, which was perceived differently by "early birds" and "night owls" in Hong Kong, and more relatable to USA respondents than to Hong Kong respondents. Highlights: This study compared visitors' perceptions of the same view (i.e., Hong Kong cityscape) at daytime and nighttime. Hong Kong respondents perceived "night" to be more feminine, mysterious, imaginative, vulnerable and superficial than "day". "Night owls" perceived "day" to be more masculine, powerful, hardworking, vulnerable, glamorous and independent. American respondents perceived "night" to be more successful and glamorous than Hong Kong respondents did. Hong Kong respondents perceived "night" to be more superficial and vulnerable than American respondents did.